Analysis of factors in integrated internship models for preservice Islamic education teachers using exploratory factor analysis - Karwadi Karwadi; Abd Razak Zakaria; Adhi Setiawan; Moh. Ferdi Hasan (International Journal of Evaluation and Research in Education (IJERE), 2026)
This research identifies key success factors of integrated internship models for prospective Islamic Religious Education (PAI) teachers using exploratory factor analysis (EFA), addressing critical gaps where empirical evidence in religious teacher preparation remains limited. Analyzing 218 PAI students across four Yogyakarta universities through mixed-methods design, EFA revealed a four-factor structure explaining 63.4% variance: observation competence (28.7%), microteaching (13.8%), teaching practice (11.2%), and spiritual reflection (9.7%). The identification of spiritual reflection as an independent factor represents a novel contribution not documented in international teacher education literature, empirically validating integration of spiritual competencies within professional preparation frameworks. The internship component assessment scale (ICAS) demonstrates strong psychometric properties (CVI=0.87, α=0.84), providing the first culturally responsive instrument for Islamic education contexts. This study proposes the integrated internship spiral model (IISM) emphasizing cyclical reinforcement rather than linear progression, challenging conventional designs. Educational implications include redesigning PAI teacher professional education curriculum with proportional resource allocation, implementing mentor training for assessing spiritual-pedagogical dimensions, and embedding technology integration across internship phases. Future research should pursue longitudinal validation, cross-contextual studies in other religious education settings, instrument development strengthening spiritual factor reliability, and comparative effectiveness studies. This research demonstrates that culturally responsive teacher preparation can honor religious authenticity while advancing professional excellence, contributing to holistic transformation of PAI internship programs with potential global application.